MODEL STRUKTUR SPASIAL POLA PERKEMBANGAN LAHAN PERKOTAAN BARU TERPADU DI KABUPATEN MAMUJU BERBASIS GEOGRAPHIC INFORMATION SYSTEM - Deril, Virda Evi Yanti (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2024)
Land development patterns are patterns formed in the land use structure of a region, both planned and unplanned. Changes in the spatial structure of land development in the Integrated Urban Area as an implementation of PKNp in the West Sulawesi Provincial RTRW in supporting regional economic development are one of the main factors in attracting the priority of West Sulawesi Province's development direction to the Integrated New City development area which is directed at 2 (two) sub-districts in Mamuju Regency, including Mamuju District and Kalukku District. The MATABE Urban Area is designated as the National Promotion Activity Center (PKNp) area which functions as an industrial area, trade, main transportation hub on a national scale and the main hub for export-import activities or a gateway to the international region, as an effort by the government to improve the regional economy. This study aims to identify land development patterns formed in the development of the Integrated New Urban Area in Mamuju Regency and analyze their impact on the spatial structure in Mamuju Regency internally and West Sulawesi Province externally using a quantitative descriptive method with spatial analysis techniques in the form of GIS (Geographic Information System)-based modeling. Where, this analysis is a technique used to explore data from a spatial perspective. The results of the analysis show that the spatial structure model of land development patterns in the New Urban Area in Mamuju Regency basically refers to the polycentric model (random movement) which is influenced by the existence of public service centers and Mamuju Urban services which are spread with a mono-centered model, which means that the area consists of one center and several sub-centers that are not connected to each other between one sub-center and another.